RETRACTED: MiR-365a-3p-Mediated Regulation of HELLS/GLUT1 Axis Suppresses Aerobic Glycolysis and Gastric Cancer Growth - Yang, Rui; Liu, Gen; Han, Limin; Qiu, Yuheng; Wang, Lulin; Wang, Mei (Frontiers in Oncology, 2021)
Gastric cancer (GC) is a common and invasive malignancy, which lacks effective treatment and is the third main reason of cancer death. Metabolic reprogramming is one of the main reasons that GC is difficult to treat in various environments. Particularly, abnormal glycolytic activity is the most common way of metabolism reprogramming in cancer cells. Numerous studies have shown that microRNAs play important roles in reprogramming glucose metabolism. Here, we found a microRNA-miR-365a-3p, was significantly downregulated in GC according to bioinformatics analysis. Low expression of miR-365a-3p correlated with poor prognosis of GC patients. Overexpression of miR-365a-3p in GC cells significantly inhibited cell proliferation by inducing cell cycle arrest at G1 phase. Notably, miR-365a-3p induced downregulation of HELLS through binding to its 3' untranslated region (UTR). Additionally, we found that miR-365a-3p suppressed aerobic glycolysis by inhibiting HELLS/GLUT1 axis. Lastly, we shown that overexpression of miR-365a-3p significantly inhibited tumor growth in nude mice. Conversely, Reconstituted the expression of HELLS rescued the suppressive effects of miR-365a-3p. Our data collectively indicated that miR-365a-3p functioned as a tumor suppressor in GC through downregulating HELLS. Therefore, targeting of the novel miR-365a-3p/HELLS axis could be a potentially effective therapeutic approach for GC.